Comparative analysis of cantilever bridge slab thickness based on the finite element method (Research, Society and Development, 2021)
The construction process of reinforced concrete highway bridges requires study and analysis of the action of permanent and variable loads, in addition to other factors such as the dynamic actions arising from the movement and traffic of vehicles on the deck. The spread of capitalism, associated with the phenomenon of globalization causes the exponential growth of vehicle flow, consequently greater structural demands, these factors have great relevance in planning and development in the design of superstructure construction, because they are inherent to the emergence of transverse moments aroused in the longitudinal direction of the cantilever bridge slabs. The search for the correct analysis and consideration of these aspects for the structural evaluation of a bridge motivated the development of this study, for a better understanding of the efforts aroused in the structural element, as well as the efficient solution for it. The analysis of the variation in the thickness of cantilever bridge slabs is a preponderant factor in the foundation of this research. The study approached the semi-analytical mathematical model developed by Bakht and Jaeger (1985) and compared with the results obtained by Robalo (2013) by means of software based on the finite element method, a comparison and analysis of bending moments aroused in the cantilever slab was performed, correlating the factors related to the emergence of these efforts. The research used the Microsoft Excel program and the results obtained by Robalo (2013) with the SAP2000 software. It is concluded in this work the proportionality of the variation of slab thickness with the intensity of peak moments and the appearance of cracks in the structural part.